2015
DOI: 10.1002/hec.3300
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Social Status Matter to Longevity?—Evidence from China's Academician Election

Abstract: We provide evidence for the causal impact of social status on longevity by exploiting a natural experiment in which subjects undergo a shift in their social status without considerable economic impact. We gather data on 4190 scientists who were either nominated for or successfully elected to the Chinese Academy of Science or of Engineering. Being elected as an academician in China is a boost in social status (vice-ministerial level) with negligible direct economic impact (US$30 monthly before 2009). After corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Human status can also be based on prestige, or freely conferred deference from others (Henrich & Gil-White, 2001 ; Cheng & Tracey, 2013 ). Studies in WEIRD (Western, educated, industrialized, rich and democratic) societies (Henrich et al, 2010 ) have shown that individuals with higher social status based on prestige, rather than money, live longer than economically equal peers without prestige (Liu et al, 2017 ; Redelmeier & Singh, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human status can also be based on prestige, or freely conferred deference from others (Henrich & Gil-White, 2001 ; Cheng & Tracey, 2013 ). Studies in WEIRD (Western, educated, industrialized, rich and democratic) societies (Henrich et al, 2010 ) have shown that individuals with higher social status based on prestige, rather than money, live longer than economically equal peers without prestige (Liu et al, 2017 ; Redelmeier & Singh, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rablen and Oswald (2008), for example, compare scientists who won the Nobel prize in Chemistry and Physics to scientists who were nominated, finding a causal effect of winning a Nobel prize on longevity. Liu et al (2017) estimate the effect among scientists of being elected to the Chinese Academy of Science and Engineering and find that becoming an academician increases longevity with approximately 1.2 years.…”
Section: Longevity Returns To Political Officementioning
confidence: 99%
“…However, the plethora of confounding factors affecting life expectancy makes it difficult to make causal inferences 9 . For instance, socioeconomic factors, such as socioeconomic status (SES), educational attainment, income, and occupation, play a significant role as confounding variables in longevity studies 10 12 . SES can have a substantial impact on various aspects of individuals’ lives, including access to healthcare, living conditions, lifestyle choices, and exposure to environmental hazards, all of which can influence longevity outcomes 13 .…”
Section: Introductionmentioning
confidence: 99%